Incidence and predictors of 6 months mortality after an acute heart failure event in rural Uganda: The Mbarara Heart Failure Registry (MAHFER) - Abeya, Fardous Charles; Lumori, Boniface Amanee Elias; Akello, Suzan Joan; Annex, Brian H.; Buda, Andrew J.; Okello, Samson (International journal of cardiology, 2018)
Objective: We sought to estimate the incidence and predictors of all-cause mortality 6 months after heart failure hospitalization in Uganda. Methods: Mbarara Heart Failure Registry is a cohort of patients hospitalized with a clinical diagnosis of heart failure at Mbarara Regional Referral Hospital, Uganda. We measured serum electrolytes, cardiac markers, and echocardiograms. All participants were followed until death or end of 6 months. We used Fine and Gray models to estimate the incidence and predictors all-cause mortality. Results: A total of 215 participants were enrolled, 141 (66%) were women, and mean age 53 (standard deviation 22) years. Nineteen (9%) had diabetes, 40 (19%) had HIV, and 119 (55%) had hypertension. The overall incidence of all-cause mortality was 3.58 (95% CI 2.92, 4.38) per 1000 person-days. Men had higher incidence of death compared to women (4.02 vs 3.37 per 1000 person-days). The incidence of all-cause mortality during hospitalization was almost twice that of in the community (27.5 vs 14.77 per 1000 person-days). In adjusted analysis, increasing age, NYHA class IV, decreasing renal function, smoking, each unit increase in serum levels of Potassium, BNP, and Creatine kinase-MB predicted increased incidence of 6 months’ all-cause death whereas taking beta-blockers and having an index admission on a weekend compared to a week day predicted survival. Conclusions and interpretation: There is a high incidence of all-cause mortality occurring in-hospital among patients hospitalized with heart failure in rural Uganda. Heart failure directed therapies should be instituted to curb heart failure-related mortality.
Keywords: 6 months mortality; Acute heart failure; MAHFER; Predictors